Phylogenetic Resolution in Juglans Based on Complete Chloroplast Genomes and Nuclear DNA Sequences - Dong, Wenpan; Xu, Chao; Li, Wenqing; Xie, Xiaoman; Lu, Yizeng; Liu, Yanlei; Jin, Xiaobai; Suo, Zhili (Frontiers in Plant Science, 2017)
Walnuts (Juglans of the Juglandaceae) are well-known economically important resource plants for the edible nuts, high-quality wood, and medicinal use, with a distribution from tropical to temperate zones and from Asia to Europe and Americas. There are about 21 species in Juglans. Classification of Juglans at section level is problematic, because the phylogenetic position of J. cinerea is disputable. Lacking morphological and DNA markers severely inhibited the development of related researches. In this study, the complete chloroplast genomes and two nuclear DNA regions (the internal transcribed spacer and ubiquitin ligase gene) of ten representative taxa of Juglans were used for comparative genomic analyses in order to deepen the understanding on the application value of genetic information for inferring the phylogenetic relationship of the genus. The Juglans chloroplast genomes possessed the typical quadripartite structure of angiosperms, consisting of a pair of inverted repeat regions separated by a large single-copy region and a small single-copy region. All the ten chloroplast genomes possessed 112 unique genes arranged in the same order, including 78 protein-coding, 30 tRNA, and 4 rRNA genes. A combined sequence data set from two nuclear DNA regions revealed that Juglans plants could be classified into three branches: (1) section Juglans, (2) section Cardiocaryon including J. cinerea which is closer to J. mandshurica, and (3) section Rhysocaryon. However, three branches with a different phylogenetic topology were recognized in Juglans using the complete chloroplast genome sequences: (1) section Juglans, (2) section Cardiocaryon, and (3) section Rhysocaryon plus J. cinerea. The molecular taxonomy of Juglans is almost compatible to the morphological taxonomy except J. cinerea (section Trachycaryon). Based on the complete chloroplast genome sequence data, the divergence time between section Juglans and section Cardiocaryon was 44.77 Mya ago, while section Rhysocaryon diverged from other sections in the genus Juglans was 47.61 Mya ago. Eleven of the twelve small inversions in the chloroplast genomes provided valuable phylogenetic information for classification of walnut plants at section and species levels. Our results are valuable for future studies on Juglans genetic diversity and will enhance the understanding on the phylogenetic evolution of Juglandaceae.